European consensus-based recommendations for diagnosis and treatment of immunoglobulin A vasculitis—the SHARE initiative - Ozen, Seza; Marks, Stephen D.; Brogan, Paul; Groot, Noortje; de Graeff, Nienke; Avcin, Tadej; Bader-Meunier, Brigitte; Dolezalova, Pavla; Feldman, Brian M.; Kone-Paut, Isabelle; Lahdenne, Pekka; McCann, Liza; et al. (Rheumatology (Oxford, England), 2019)
Abstract Objectives IgA vasculitis (IgAV, formerly known as Henoch–Schönlein purpura) is the most common cause of systemic vasculitis in childhood. To date, there are no internationally agreed, evidence-based guidelines concerning the appropriate diagnosis and treatment of IgAV in children. Accordingly, treatment regimens differ widely. The European initiative SHARE (Single Hub and Access point for paediatric Rheumatology in Europe) aims to optimize care for children with rheumatic diseases. The aim therefore was to provide internationally agreed consensus recommendations for diagnosis and treatment for children with IgAV. Methods Recommendations were developed by a consensus process in accordance with the EULAR standard operating procedures. An extensive systematic literature review was performed, and evidence-based recommendations were extrapolated from the included papers. These were evaluated by a panel of 16 international experts via online surveys and subsequent consensus meeting, using nominal group technique. Recommendations were accepted when ⩾80% of experts agreed. Results In total, 7 recommendations for diagnosis and 19 for treatment of paediatric IgAV were accepted. Diagnostic recommendations included: appropriate use of skin and renal biopsy, renal work-up and imaging. Treatment recommendations included: the importance of appropriate analgesia and angiotensin-converting enzyme inhibitor use and non-renal indications for CS use, as well as a structured approach to treating IgAV nephritis, including appropriate use of CS and second-line agents in mild, moderate and severe disease along with use of angiotensin-converting enzyme inhibitors and maintenance therapy. Conclusion The SHARE initiative provides international, evidence-based recommendations for the diagnosis and treatment of IgAV that will facilitate improvement and uniformity of care.